The Four Waves of Systems Thinking - Cabrera, Derek; Cabrera, Laura; Midgley, Gerald (Journal of systems thinking, 2023)
This Handbook is about the past, present, and future of systems thinking. It captures the history of systems thinking over its first three ‘waves,’ which are thought of as significant paradigmatic time periods in the history of the field. It then introduces a (possible) emerging fourth wave. Herein, we review the first three waves, as they have been written about in depth before, and dedicate more space to describing the fourth wave, as this is likely to be new to many readers. We cover all four waves as an entree to the many chapters, which were both recommended by an International Advisory Board (listed and thanked in the front material of this book), and written by esteemed invited authors. These chapters aptly describe the various frameworks that characterize the different waves; and notably include how those frameworks have continued to evolve since their origin.
Keywords: Systems Thinking; DSRP; The Four Waves; Universality; The Fourth Wave